Noise and Vibration Analysis of Electric Oil Pump with Asymmetric Pitch Control for Gearbox in Hybrid and Battery Electric Vehicle - Chinchul Choi (Applied Sciences)
This study proposes an asymmetric pitch control technique for electric oil pumps with symmetric gear-type pumps in order to reduce noise and vibration. For vane pump noise reduction, mechanical asymmetric pitch arrangements of each vane are widely used. However, the mechanical asymmetric pitch arrangement approach is not applicable in gear-type pumps due to structural limitations. The proposed asymmetric pitch control method provides similar effects to the mechanical asymmetric pitch arrangement by employing instantaneous motor torque controls for an electric oil pump with a gear-type pump. The magnitude of motor torque for each pump tooth is determined with an asymmetric pitch formula, which has been widely used for mechanical vane pumps in previous studies and patents. A formula for the shape of instantaneous motor torque is proposed for the analysis of pressure fluctuations of pumps, which is a combination of trigonometric and exponential functions. The calibration factors for the magnitude and shape can be adjusted according to the characteristics of a given pump. The experimental results for a 400 W electric pump show that the proposed method reduced and dispersed the noise peak by approximately 4 dB(A) in comparison with the normal control, and affected hydraulic performance with a less than 1% decrease in flow rate in not only pump-level but also gearbox-level test environments.